2021
DOI: 10.3389/fmed.2021.683357
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Solution for Lupus Anticoagulant Testing in Patients Taking Direct Oral FXa Inhibitors Using DOAC Filter

Abstract: Background: Direct oral factor Xa (FXa) inhibitors interfere with lupus anticoagulant (LA) assays challenging antiphospholipid syndrome diagnosis in treated patients. We evaluated a new device, called DOAC Filter, and its usefulness in this setting. It is a single-use filtration cartridge in which FXa inhibitor compounds are trapped by non-covalent binding while plasma is filtered through a solid phase. Patient samples were analyzed before and after filtration: 38 rivaroxaban, 41 apixaban, and 68 none. Anticoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In practice, the 15‐minute one‐step DF procedure may be preferred to a 20‐minute two‐step (incubation and centrifugation) procedure of DS. However, a 22.6% volume loss after filtration with a mean recovered volume of 465 µL, in line with observations of Sevenet et al 34 and Farkh et al, 46 could be a limiting factor in clinical practice. In this regard, a full three‐step LAC testing in two systems may need the use of 2 DFs, which is economically less interesting and may lead to insufficient sample volume (2 × 600 µL PPP).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In practice, the 15‐minute one‐step DF procedure may be preferred to a 20‐minute two‐step (incubation and centrifugation) procedure of DS. However, a 22.6% volume loss after filtration with a mean recovered volume of 465 µL, in line with observations of Sevenet et al 34 and Farkh et al, 46 could be a limiting factor in clinical practice. In this regard, a full three‐step LAC testing in two systems may need the use of 2 DFs, which is economically less interesting and may lead to insufficient sample volume (2 × 600 µL PPP).…”
Section: Discussionsupporting
confidence: 85%
“…Discordances within the nonanticoagulated patient group, with final LAC results becoming negative after filtration, mostly originated from a shorting in dRVVT screen CT. Shorter postfiltration CTs of the LAC assays, however clinically nonsignificant, were also observed by Sevenet et al 34 In addition, the recently published work of Farkh et al 46 on the effect of DF on LAC testing reported no statistically significant differences for dRVVT and silica clotting time (SCT) screen or screen/confirm ratios in a control group of 68 nonanticoagulated patient samples. However, 4 of 37 dRVVT and 5 of 15 SCT (weakly) positive screen ratios changed to negative after filtration.…”
Section: Discussionmentioning
confidence: 68%
“…Since the beginning of the use of DOAC, their presence has been described to affect coagulation tests [11,12]. Several publications have established their influence on individual tests ranging from determination of factor levels to thrombophilia [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Another activated charcoal‐based product called DOAC‐Remove has subsequently been produced by another commercial manufacturer (5‐Diagnostics, Switzerland), and seems to have similar features to DOAC‐Stop 38 , 39 , 44 , 45 , 46 , 47 , 48 , 49 , 50 (Table 3 ; Table S2 ). A third product is available from a third manufacturer (Stago Diagnostics) and is called DOAC‐filter 51 , 52 (Table 3 ; Table S2 ). A different type of filter has recently been released for sale by 5‐Diagnostics, called DP‐filter; studies on the device appear to only have been published in abstract form.…”
Section: Anticoagulant Neutralizersmentioning
confidence: 99%